NILAI-NILAI ISLAM DALAM NOVEL SCAPPA PER AMORE: ANALISIS SEMIOTIKA FERDINAND DE SAUSSURE - Gina Washilatul Kamila; Dadan Rusmana; Myrna Nursakinah (ALFABETA: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2021)
Abstract The purpose of this research is to analyze the Islamic values implied in the Scappa per Amore: Mozaik Perjalanan Cinta di Benua Biru. The research problems that will be explored are (1) How to interpret the signs that appear in each quotation, (2) What Islamic values can be understood from each quotation, and (3) What are the evidences underlying Islamic values that appear in each quotation. This research employs Ferdinand de Saussure’s dichotomous semiotic theory, which distinguished between signifier and signified and employs qualitative method. The data used in this research are eight quotations from the Scappa per Amore novel by Dini Fitria which consist of five sections and twenty-nine chapters. According to the findings of this research, each of these quotation contains Islamic values, as well as the underlying evidences. These values can be interpreted as messages that the reader can take away from the novel as wisdom and guidelines for daily living. Keywords: Signs, Novel, Quotation, Evidence.